Costa Rica : Overview of Tobacco Use, Tobacco Control Legislation, and Taxation - World Bank Group (World Bank, Washington, DC, 2019)
This brief provides an overview of tobacco control legislation, use, and taxation in the country. Costa Rica ratified the WHO Framework Convention on Tobacco Control in 2008. General Law for the Control of Tobacco and its Harmful Effects on Health was adopted in March 2012, and it regulates smoke-free places; tobacco advertising, promotion, and sponsorship, as well as tobacco packaging and labeling in line with FCTC guidelines. This law also sets several norms on tobacco taxation, and it substantially increased the tax burden for cigarettes. In 2012, cigarette prices in Costa Rica increased by 49 percent, and in 2013, the tobacco excise revenue increased by 96 percent. Tobacco taxation and other tobacco control policies in Costa Rica were very successful in terms of public health. The prevalence of smoking both among adults and adolescents declined, and after 2012, the rates of decline increased. In 2015, only 5.8 percent of the adult population smoked daily. In 2018, cigarette production in the country was closed. The tobacco industry claimed that the closure had been caused by increased cigarette smuggling. However, there are no independent estimates of illicit cigarette share on the market, while the tobacco industry used to exaggerate the volumes of smuggled cigarettes. The difference in cigarette prices between Costa Rica and neighboring countries is rather small and is unable to encourage large smuggling. Thus, the observed illicit cigarette sales are likely caused by the factors, which are not related directly to tobacco taxation.